Correlation between metformin use and mortality in acute respiratory failure: a retrospective ICU cohort study - Yunlin Yang; Jinfeng Liu; Yi Hou; Yuxun Wei; Liang Huang; Liang Huang; Wei Wei (Frontiers in Pharmacology)
BackgroundThe aim of this study was to investigate the association of metformin use with the risk of in-hospital mortality and prognosis in acute respiratory failure (ARF) patients admitted to the intensive care unit (ICU).MethodsWe conducted a retrospective cohort study using the MIMIC-IV database. Patients were categorized into metformin and non-metformin groups based on medication exposure. Primary outcomes were in-hospital and ICU mortality, while 30-day and 90-day all-cause mortality served as secondary endpoints. We applied Kaplan–Meier survival curves, Cox proportional hazards models, and logistic regression to assess associations. Propensity score matching (PSM) and machine learning algorithms were used for confounder adjustment and feature selection.ResultsAfter PSM, 1,429 patients with ARF were included (374 metformin users; 1,055 non-users). Multivariate logistic regression revealed that metformin use was associated with significantly reduced in-hospital mortality (OR = 0.202, 95% CI: 0.123–0.317, p < 0.001) and ICU mortality (OR = 0.245, 95% CI: 0.142–0.399, p < 0.001). Cox models showed consistent reductions in 30-day (HR = 0.199, 95% CI: 0.124–0.320, p < 0.001) and 90-day (HR = 0.230, 95% CI: 0.150–0.352, p < 0.001) mortality. Kaplan–Meier curves confirmed better survival in the metformin group (p < 0.001). Subgroup analyses supported a consistent protective effect of metformin across most patient strata.ConclusionMetformin use was significantly associated with decreased short-term mortality among ICU patients with ARF. These findings suggest that metformin, beyond its glucose-lowering effects, may offer survival benefits in critically ill populations. Clinicians should consider the potential role of metformin when managing ICU patients with type 2 diabetes and ARF. Further prospective studies are warranted to confirm these findings and optimize clinical application strategies.